Female Adolescent Soccer Players Utilize Different Neuromuscular Strategies Between Limbs During the Propulsion Phase of a Lateral Vertical Jump - Matthew D DeLang; Joseph P Hannon; Shiho Goto; James M Bothwell; J Craig Garrison (International Journal of Sports Physical Therapy)
# Background